1991
DOI: 10.1002/jso.2930460318
|View full text |Cite
|
Sign up to set email alerts
|

Biliary and pancreatic metastases of breast carcinoma: Is surgical palliation indicated?

Abstract: Obstructive jaundice developed in a patient concomitantly with the diagnosis of breast carcinoma. Abdominal exploration disclosed a metastatic tumor in the head of the pancreas, the distal bile duct, and the gallbladder. A cholecystectomy and choledochojejunostomy were performed and later, because of intestinal obstruction, the patient underwent gastrojejunostomy. Pathological examination demonstrated metastatic lobular carcinoma of breast with strongly positive staining for estradiol. Additional hormonal ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…In autopsy series of patients with breast cancer, metastatic spread to the pancreas can be detected in 11-17%, which is comparable to the frequency of metastases to the kidneys or the heart muscle and ranges far behind metastasis to lymph nodes, lung, or liver [12][13][14].…”
Section: Discussionmentioning
confidence: 75%
“…In autopsy series of patients with breast cancer, metastatic spread to the pancreas can be detected in 11-17%, which is comparable to the frequency of metastases to the kidneys or the heart muscle and ranges far behind metastasis to lymph nodes, lung, or liver [12][13][14].…”
Section: Discussionmentioning
confidence: 75%
“…Pappo et al [11] reported a case of an obstructive jaundice developed in a patient concomitantly with the diagnosis of breast carcinoma. After a vigorous surgical diagnostic approach, pathological examination demonstrated metastatic lobular carcinoma of breast in the head of the pancreas, the distal bile duct, and the gallbladder with strongly positive staining for estradiol.…”
Section: Discussionmentioning
confidence: 99%
“…[12] The most common mode of metastatic spread to pancreas is direct invasion from cancers of neighboring organs, followed by lymphatic and hemato-geneous dissemination as in renal-cell and lung-carcinoma. [34]…”
mentioning
confidence: 99%
“…To the best of our knowledge, there have been only few cases of pancreatic-metastasis from carcinoma breast reported in the literature so far. [23456]…”
mentioning
confidence: 99%
See 1 more Smart Citation